Sisterhood in Academia. Understanding and Experiencing Women’s Collaboration in the Social Sciences - Kroczak, Hanna; Szczepaniak, Colette; Cybort-Zioło, Natalia; Makowska, Aneta; Adamska-Kijko, Magdalena; Bochno, Ewa; Czerepaniak-Walczak, Maria (Przegląd Badań Edukacyjnych (Educational Studies Review), 2025)
This article presents selected findings from research on sisterhood in academia, exploring how it is understood and experienced by women working in research and teaching positions in the social sciences. The article addresses two research questions: How do women working in Polish universities define sisterhood? What are the experiences of the interviewees in this regard? The overarching research method was exploratory interviewing, which we conducted using individual in-depth interviews based on a semi-structured scenario with open-ended questions. We interviewed twenty women working in various academic positions at Polish universities. In the text, we present the findings of the exploratory research on the understanding of sisterhood, as well as the narrators’ experiences within the context of cooperation between women, solidarity, and sisterhood-based relationships.